Phytochemical Screening and Assessment of Adhatoda Vasica (Leaf) For Antihistaminic Activity - Athiya, Vandana; Gupta, Sailesh; Chourasiya, Anand (Journal of Drug Delivery and Therapeutics, 2019)
Biologically active compounds from natural sources are of interest as possible new drugs for different diseases. Over many centuries humans have been mining the bounties of nature for discovering natural products that have been used for the treatment of all human diseases. Adhatoda vasica Nees (Acanthaceae) is widely used in the Indian system of medicine as an Asthma, bleeding, bronchitis, cough, diarrhea, dysentery, fever, flu, hysteria, neuralgia, rheumatic pain, swelling, TB, urinary disorders, vomiting etc. The plant was also reported for its diabetes, epilepsy, skin disorders and many more such activities. Clonidine, a α2 adrenoreceptor agonist induces dose dependent catalepsy in mice, which was inhibited by histamine H1 receptor antagonists but not by H2 receptor antagonist. Clonidine releases histamine from mast cells which is responsible for different asthmatic conditions. In present study methanol extract of Adhatoda vasica leave at doses 100and 200 mg/kg i.p were evaluated for antihistaminic activity using clonidine induced catalepsy in mice. Acute toxicity of the extract (2000 mg/kg) was examined in mice for 7 days. Qualitative analysis of various phytochemical constituents was determined by the well-known test protocol available in the literature. Phytochemical analysis revealed the presence of carbohydrates, glycosides, alkaloids, saponins, flavonoids, tannin and phenolic compounds. Methanolic extract up to 2000 mg/kg did not produce any toxic effects. The methanolic extract of leave of Adhatoda vasica (100, 200 mg/kg, p.o.) and chlorpheniramine maleate (10 mg/kg, i.p.) significantly inhibited (**P< 0.05) clonidine-induced catalepsy in mice at 180 min after the administration of clonidine. The methanolic extract of leave of Adhatoda vasica possesses significant antihistaminic activity (H1-antagonist) and can be attributed to bronchodilating, anti-inflammatory, adaptogenic activity etc. Hence detailed study needs to be conducted to evaluate the phytoconstituent responsible for the above mentioned results and their clinical efficacy in the treatment of related diseases. Keywords: Adhatoda vasica, Clonidine, Antihistaminic activity, Chlorpheniramine maleate, Qualitative analysis.